Controls on submarine canyon morphology along a convergent tectonic margin. The Southern Caribbean of Colombia. (March 2022) - Naranjo-Vesga, J.; Paniagua-Arroyave, J.F.; Ortiz-Karpf, A.; Jobe, Z.; Wood, L.; Galindo, P.; Shumaker, L.; Mateus-Tarazona, D.
Abstract: Submarine canyons are major conduits for sediment transfer from continental shelf to deep marine environments. Mass failures and faults play a key role in the initiation and evolution of submarine canyons along convergent tectonic margins, in addition to continental sediment supply. Here we analyze high-resolution bathymetry and seismic data from the Colombian southern Caribbean to investigate the controls on submarine canyon morphology along a convergent tectonic margin. We propose three end-member types of canyons: Type I canyons have a direct connection to a major river associated with high sediment supply. These canyons are highly erosive and cut topographic barriers created by tectonic deformation. Type II canyons are associated with faults at the canyon's head, where the location, orientation, and sinuosity are controlled by fault strike. Also, the presence of faults is related to an increase in the occurrence of mass failures from the steep canyon borders, increasing the depth and width asymmetry. Finally, Type III canyons evolve toward the continental shelf edge through retrogressive mass failures. These mass failures produce erosional scars that merge downslope to create submarine canyons in early stages of development, which later evolve to wider but shallow canyons due to the progressive basinward merging. We argue that the morphology of each canyon type is controlled by the interaction between continental sediment supply, mass failures, shelf width, and fault occurrence. We also demonstrate that seafloor topography influences the size of submarine fan deposits at the mouths of canyons. We identified large fan deposits (>650 km 2 ) on the continental rise, whereas in piggyback sub-basins we found smaller fans (<60 km 2 ). Our analysis of downdip canyon morphology and associated deposits can be used to predict the development of submarine canyons and associated fans in convergent tectonic margins worldwide. Highlights: Bathymetry and seismic data quantify submarine canyons on a convergent margin. Three canyon types exist due to geomorphologic variability along the margin. Sediment flux and shelf-slope topography affect canyon morphology and fill. Submarine fan dimensions controlled by topographic confinement, or lack thereof.